Isolated benign neutropenia in healthy individuals from Saudi Arabia’s central region: A comprehensive study - Alshomar, Ahmad (International Journal of Health Sciences, 2023)
Objectives: Neutrophils are the most common cell types in circulation and are considered the first line of defense in the immune system against microorganisms. This study was undertaken to investigate the occurrence of isolated benign neutropenia (IBN) among healthy individuals in the central region of Saudi Arabia. Methods: This retrospective study analyzed complete blood count tests as part of routine checkups for chronic health conditions from April to September 2022. The 10,442 participants were randomly selected and their medical records were reviewed for neutropenia and mean absolute neutrophil counts (ANCs) were calculated. Descriptive analysis was employed to assess the prevalence of IBN across various demographic factors, such as age, gender, and nationality. Results: The prevalence of IBN in the central region of Saudi Arabia was found to be 2.82% across the entire cohort of participants. The mean ANC among all participants was 4.55 × 109 /L. The prevalence of neutropenia was higher in male participants compared with female. Male neutropenic had a lower mean ANC than female; however, the differences were not statistically different (P > 0.05). The prevalence of neutropenia was lower in Saudi participants compared with non-Saudis. While the mean ANC was lower among Saudis as compared with non-Saudi participants. However, the differences were not statistically different (P > 0.05). Conclusion: This is the first study from the central region of Saudi Arabia that determined the prevalence of chronic benign neutropenia among healthy individuals. The prevalence of IBN was found to be relatively low. Furthermore, neutropenia was more frequent in males than females. Moreover, male neutropenic individuals have a lower ANC.